Peran Kelompok Tani Turi Mania Dalam Usahatani Padi Sawah Di Desa Bunia Kecamatan Bintauna Kabupaten Bolaang Mongondow Utara - Kantohe, Christelina Tirta Mulia; Manginsela, Elsje Pauline; Tangkere, Ellen Grace (Sam Ratulangi University, 2024)
This study aims to describe the role of the Turi Mania Farmers' Group in rice farming in Bunia Village, Bintauna Sub-district, Bolaang Mongondow Utara Regency. The research was conducted over a period of 3 months from September to November 2023, based in Bunia Village, Bintauna Sub-district, Bolaang Mongondow Utara Regency. The data for this study were collected through primary data obtained from direct interviews with members of the Turi Mania Farmers' Group about their roles in rice farming, using a prepared questionnaire. Secondary data were obtained from the Bunia Village government office and from online sources such as journals and research theses. The sampling method used was a census method, involving all members of the Turi Mania Farmers' Group in Bunia, from the management to the members, totaling 14 respondents. Data analysis was conducted using a qualitative descriptive approach, presented in the form of tables. The data obtained were analyzed using a Likert scale. This analysis explains the role of the Turi Mania Farmers' Group based on learning classes, cooperation platforms, and production units. The results show that the role of the Turi Mania Farmers' Group in Bunia Village, Bintauna Sub-district, Bolaang Mongondow Utara Regency in rice farming is categorized as a learning class with a total score of 121 and a role index of 95.74%, fairly significant as a cooperation platform with a total score of 82 and a role index of 67.74%, and significant as a production unit with a total score of 113 and a role index of 89.68%.